Video on demand (VOD): an analysis of the regulatory system in the United Kingdom - Nazli, Ismail@Nawang (2012)
Video on demand ('VOD') is a new technology that enables viewers to watch audio-visual ('television-like') content at their own preferred time. VOD services are currently accessible over a variety of distribution platforms including the Internet, Internet Protocol television ('IPTV'), cable, satellite and digital terrestrial television ('DTT'), smart phones and many others. The availability of high-speed broadband connections and rapid technological advancements has enabled viewers to watch programmes which are similar to those that are broadcasted on traditional televisions via VOD services. Nonetheless, VOD does not fall within the regulatory regime of the traditional broadcast media. This is certainly undesirable as VOD has a huge potential to become a serious rival to the traditional broadcast media. As such, this study attempts to examine in detail the regulatory system that has been formulated to regulate VOD in the United Kingdom ('UK').